The Impact Of Women Leaders On Business Performance - Vu Minh Trang, Tran (Digital Repository of Theses - SSBM Geneva, 2025)
The persistent underrepresentation of women in business leadership is shaped by dominant paradigms that prioritize masculine-coded traits and overlook the influence of social identities and power structures. This study addresses the gap in understanding the specific competencies women develop to navigate exclusionary leadership environments. On methodology, the research integrates quantitative data from mid- to senior-level leaders with qualitative insights from in-depth interviews with women leaders. The quantitative phase assesses gender differences in transformational leadership, emotional intelligence, strategic acumen, and adaptive capacity using validated instruments. The qualitative phase explores women’s lived experiences of skill acquisition and strategies for overcoming systemic barriers. By integrating both quantitative and qualitative data strands, this study endeavors to construct a robust and comprehensive model of gender-inclusive leadership. This synthesized model will illuminate the intricate mechanisms through which individual competencies intersect with broader organizational structures. Concurrently, it aims to offer context-specific strategies for fostering genuine equity in leadership development programs. Ultimately, this research seeks to inform adaptive, evidence-based practices. These interventions are designed to directly challenge deep-seated structural limitations and cultivate a truly inclusive leadership pipeline within diverse organizational settings. Keywords: Gendered leadership; Women in leadership; Leadership competencies; Feminist theory; Intersectionality; Mixed-methods; Inclusive leadership; Organizational equity